Streamlining environmental management legislation in Zimbabwe: the case of the new Environmental Management Act Chapter 20:27/2002 - Madebwe, C.; Madebwe, V.; Madebwe, T. M. (IOS Press, 2021)
In 2003, Zimbabwe legislated the new EMA (Environmental Management Act). However, today, two years after it was promulgated, the EMA has yet to become operational, thus destabilizing the environmental management sector. Using literature review and document analysis, this paper critically assesses the adequacy of the provisions of EMA against the components of FAO's (Food and Agriculture Organization) legal framework of environmental management principles and standards, which emerged as a result of the Rio Declaration. Prior to the promulgation of EMA, the functions of environmental institutions were mired in conflict with overlapping and inter-sectoral competition. EMA rationalized, consolidated, and established a hierarchy in environmental legislation.